IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING (SAW) METHODE IN DETERMINING HIGH SCHOOL STUDENT’S INTEREST - Prind Triajeng Pungkasanti (Universitas PGRI Semarang, 2017)
The Ministry of Research, Technology, and Higher Education of Republic of Indonesia has set a regulation about curriculum applied in education field named Kurikulum 2013. One of the subsections in the Kurikulum 2013 regulates all requirements of majoring in high school. High school students determine their major based on Kurrikulum 2013 as they are on the 10th grade. The purpose of the majoring in education is to allow children development based on their skills and interests, because before, majoring have been done based on scores obtained. The main problem is the majoring requirements considered are admission test score and Junior High School National Test score. Both scores are not sufficient enough to determine the students major therefore academic aptitude test score is required. In term of weighting, the school has not been imposed the weighting system so the scores obtained is the average of admission test score and national test score.Based on the issue above, a solution required to solve the issue using a method. Method used in this research is Simple Additive Weighting (SAW), wherein this methode is looking for the weighted sum of performance rate on every alternative of atributes. This research provides the information about which potential students is suitable to enter the science major and social major so this results can be used as consideration of school decisions.